Inovasi Rekrutmen Aparatur Sipil Negara Menggunakan Sistem Computer Assisted Test (CAT) - Marantika, Jerry; Frinaldi, Aldri (Lembaga Yasin AlSys, 2024)
CAT BKN is an innovation that contributes to the transformation of the ASN selection system in Indonesia. This innovation plays a very important role in preventing undesirable things, such as fraud in the CASN recruitment and selection process. Carrying out exams which usually use answer sheets and piles of question papers has become a selection system based on computer applications that is effective and efficient and reduces the opportunity for nepotism in recruitment. This article aims to look at the dynamics of the innovation process that occurred when CAT was formed as a method for CASN selection.